Analgesic-like activity of perillyl acetate: In vivo and in silico studies - Renan Braga; Humberto Andrade; Ryldene Cruz; Mayara Maia; Carolina Lima; Anderson Santos; André Miranda; Allana Duarte; Marcus Scotti; Reinaldo Almeida; Damião Sousa (Asian Pacific Journal of Tropical Biomedicine, 2022)
Objective: To evaluate the antinociceptive activity of perillyl acetate in mice and in silico simulations. Methods: The vehicle, perillyl acetate (100, 150 and/or 200 mg/ kg, i.p.), diazepam (2 mg/kg, i.p.) or morphine (6 mg/kg, i.p.) was administered to mice, respectively. Rotarod test, acetic acid-induced abdominal writhing, formalin-induced nociception, hot plate test, and tail-flick test were performed. Opioid receptors-involvement in perillyl acetate antinociceptive effect was also investigated. Results: Perillyl acetate did not affect the motor coordination of mice. However, it reduced the number of acetic acid-induced abdominal twitches and licking times in the formalin test. There was an increase of latency time in the tail-flick test of 30 and 60 minutes. Pretreatment with naloxone reversed the antinociceptive effect of perillyl acetate (200 mg/kg). In silico analysis demonstrated that perillyl acetate could bind to μ-opioid receptors. Conclusions: Perillyl acetate has antinociceptive effect at the spinal level in animal nociception models, without affecting the locomotor integrity and possibly through μ-opioid receptors. In silico studies have suggested that perillyl acetate can act as a μ-opioid receptor agonist.